In vitro Release Kinetic Study of Esomeprazole Magnesium from Methocel K15M and Methocel K100 LVCR Matrix Tablets (Dhaka University Journal of Pharmaceutical Sciences, 2008)
In the present study esomeprazole sustained release tablet matrix was prepared by utilizing different grades of hydroxypropyl methylcellulose (HPMC) polymers such as Methocel K15M & Methocel K100 LVCR by direct compression method. Different amount of Methocel K15M was used to develop matrix builder in the seven proposed formulations (F1-F7) for the study of release rate retardant effect at 20%, 25%, 30%, 35%, 40%, 45% and 50% of total weight of tablet matrix respectively. The dissolution study of Methocel K15M based tablet matrices of those proposed formulations were carried out in the simulated gastric medium (pH 1.3) for first two hours and then in the simulated intestinal medium (pH 6.8) for 8 hours using USP dissolution apparatus II. The formulation F-5 (40%) and F-6 (45%) met the optimum release rate of esomeprazole for 10h period of in vitro dissolution study. The release kinetics of formulation F-5 and F-6 very closely followed Higuchi kinetic order than first order and zero order kinetics. Similarly Methocel K100 LVCR was used to develop matrix builder in another seven proposed formulations (F8-F14). It was found that formulations F-11 (35%), F-12 (40%) and F-13 (45%) met the desired release rate of esomeprazole for 10h period. The release kinetics of formulation F-11, F-12 and F-13 followed Higuchi kinetic order. Between these two polymers, Methocel K100 LVCR showed better release retardant effect than Methocel K15M. Key words: Esomeprazole, Direct compression, Controlled release, Methocel K15M and Methocel K100 LVCRDOI = 10.3329/dujps.v7i1.1216 Dhaka Univ. J. Pharm. Sci. 7(1): 39-45, 2008 (June) Â